Summary from Doctoral Dissertation Entitled: Between War and Diplomacy. Ferdinand the Catholic and the Foreign Policy of Spain in 1492–1516 - Kubiaczyk, Filip (Studia Europaea Gnesnensia, 2011)
Autoreferat z rozprawy doktorskiej pt. Między wojną a dyplomacją. Ferdynand Katolicki i polityka zagraniczna Hiszpanii w latach 1492–1516